The Serotonin Transporter Polymorphism (5-HTTLPR) and Alcohol Problems in Heavy Drinkers: Moderation by Depressive Symptoms - Tartter, Molly; Ray, Lara (Frontiers in Psychiatry, 2011)
Heavy alcohol use in young adults has been prospectively associated with a host of psychosocial and alcohol-related problems. Recent studies have supported the interaction between serotonin transporter polymorphism and adverse environmental factors, as a predictor of alcohol use and the development of alcohol dependence. The current study examined the role of depressive symptoms in combination with the serotonin transporter polymorphism as a predictor of alcohol use and alcohol-related problems. Results revealed a significant genotype by depressive symptom interaction, such that heavier alcohol use was associated with depressive symptoms in L allele homozygotes but not among S allele carriers. These results remained significant after controlling for ethnicity and gender effects. These findings extend the emerging literature supporting 5-HTTLPR genotype as a risk factor for alcohol-related problems in the context of co-occurring symptoms of depression.